Surgical Technique: Revision ACL Reconstruction With a Rectangular Tunnel Technique - Shino, Konsei (Springer-Verlag, 2011)
BACKGROUND: We developed the rectangular tunnel ACL reconstruction (RT ACLR) using a 10-mm wide bone-patellar tendon-bone (BTB) graft through rectangular tunnels with a rectangular aperture to reduce tunnel size: the cross-sectional area of the tunnels of 50 mm(2) (5 × 10 mm) in RT ACLR is less than that of 79 mm(2) in a conventional 10-mm round tunnel technique presuming the technique would be more suitable in revision ACLR with previous improperly placed tunnels. DESCRIPTION OF TECHNIQUE: Two contiguous 5-mm tunnels inside the anatomic ACL femoral and tibial attachment areas along their long axes, and they are expanded with a 5 × 10-mm dilator into parallelepiped ones. PATIENTS AND METHODS: We indicated and intended to perform the RT ACLR procedure in 31 patients requiring revision between 2004 and 2008. Eighteen of the 31 patients treated with the procedure were followed a minimum of 24 months (mean, 38 months; range, 24 to 73 months). We evaluated ROM, obtained IKDC scores, and determined stability with KT-1000. RESULTS: The procedure could be applied in 30 of the 31 cases. One of the 18 reruptured the graft at 28 months. Of the remaining 17 patients with followup of 24 months or longer, 15 had full ROM, while the remaining two lost 5° of flexion; 11 were classified as normal and six were nearly normal according to the IKDC evaluation. Stability measured with KT-1000 was 1.0 ± 1.5 mm. CONCLUSION: The RT ACLR technique provided acceptable results after one-stage revision ACLR. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.